Students’ Satisfaction on Learning TEFL Subject at Fifth Semester English Education Study Program in IAIN Bukittinggi - Lisa Indria Putri; Widya Syafitri (Journal of English as A Foreign Language Teaching and Research, 2021)
This study aims to determine student satisfaction in the TEFL learning process. This type of research is a quantitative descriptive study. The total population was 121 students and the research sample was 31 students in the fifth semester of English education at IAIN Bukittinggi and simple random sampling was used as a research sampling technique. Data were collected using a questionnaire. Based on the results of the study, the student satisfaction in implementing TEFL learning on good teaching items showed that students were satisfied (good) with the learning. Based on the results of this study it can be concluded that the fifth semester English students at IAIN Bukittinggi are already satisfied with the TEFL learning.